Цогт тайж улааны шашинтан байсан уу - Будсүрэн, Д. (Historia Mongolarum, 2008)
Уг өгүүлэлд XVII зууны үеийн Монголын улс төр, шашны томоохон зүтгэлтэн Цогт тайж шарын шашны эсрэг тэмцэж байсан улааны шашинтан хүн байсан уу, эсвэл энэ нь Цогт тайжийн тухайн үеийн тэмцэл. үйл ажиллагаа Монголчуудын үндэсний тэмцэл болон өргөжихөөс болгоомжлон манж нарын зүгээс шарын шашнаар түрий барин буруутгасан хэрэг байсан уу гэдгийг монгол, төвд бичгийн сурвалжийн мэдээнд тулгуурпан тодруулахыг хичээсэн болно. The main objective of the research work was to identify that the Prince Tsogt Taij, Political and Religious Leader of 17th century was really a member of the Red Buddhist against the Yellow Buddhists or a nobleman, who is critized by the Manchu people, caused anxiety that the Prince Tsogt Taij's activities strengthen the Mongol's National Revolution, based on the historical facts in Mongolian and Tibetian languages. According to this research, we found out that Tsogt Taij had friendly relations to the Yellow Buddhist and also it is known that Tsogt Taij had peaceful relations to the Guush TsorJ, the Religions Leader of the Yellow Buddhists, used to invite each other and the Red Buddhists requested the Yellow Buddhists to translate sutras. Therefore, we considered that the Prince Tsogt Taij was not agained the Yellow Buddhists and not only a guardian of the Red Buddhists in Mongolian history.